Structural equation model explanatory of student performance in the subject of General Statistics at UNALM - Salazar Vega, Rolando (2021)
The purpose of the study is to measure the adjustment of an explanatory model of student performance in the subject of General Statistics at the La Molina National Agrarian University (UNALM) through the statistical technique of Structural Equation Models. The proposed model considers four factors: student performance, teacher performance, personal perception, and past performance. Two assessment instruments are applied in the study, first to measure personal perception, and the second, is to measure teacher performance. Cronbach's Alpha Reliability Coefficient is used to verify the reliability requirement and the Confirmatory Factor Analysis to verify the validity requirement of the assessment instruments. In both assessment instruments indicators obtain to confirm their reliability and validity. The fit of the proposed model was verified using the goodness of fit indicators, finding that the proposed model had a good fit. Said adjustment improved through a process of modifying the model through the inclusion of the relationship that indicates that personal perception depends on past performance. It verified the modified model that among the factors: past performance, teacher performance, and personal perception, the former is a predictor of student’s performance. Also, in the modified model, where a new relationship includes, which was a past performance that explains the personal perception, this last relationship and the one that indicates that teacher performance explains personal perception were significant.